Salvia guaneorum (Labiatae), a new species from the Chicamocha Canyon, Colombia - Fernández-Alonso, Jose Luis (Phytotaxa, 2014)
A new species of Salvia subgen. Calosphace from the Chicamocha Canyon, in the Eastern Cordillera of Colombia is described and illustrated. The morphological affinities and putative relatives with other Colombian species of the sections Angulatae and Longipes are discussed.